Social responsibility: A gift or a necessary expense? Between good corporate governance and the determination of income tax - Benites Mendoza, Mónica (2014)
This paper seeks to contribute, through discussion, to the issue of costs related to social responsibility, a matter that has recently gained importance. In that sense, our intention is to examine to what extent such costs meet the criterion of causation, a necessary requirement to be deductible.